Transformational Leadership and Organizational Culture as Predictors of Teacher Performance: Evidence from Path and SITOREM Analysis - Rosenta Saragih; Henny Suharyati; Suhendra (Cita konsultindo, 2026)
This study examines the influence of transformational leadership and organizational culture on teacher performance among 158 teachers in A-accredited private vocational high schools in Bogor City, Indonesia. The objectives are (1) to analyze the direct and indirect effects of transformational leadership and organizational culture on teacher performance, and (2) to identify strategic improvement priorities using SITOREM. Path Analysis and SITOREM were applied. Results indicate that transformational leadership (β = 0.214; p = 0.002) and organizational culture (β = 0.243; p = 0.001) have significant direct effects on teacher performance. Work motivation and job satisfaction mediate these relationships, except for the non-significant indirect effect of self-efficacy through job satisfaction (β = 0.025; p = 0.060). SITOREM analysis identifies priority indicators for improvement based on Cost, Benefit, Urgency, and Importance (CBUI) criteria. This study contributes to vocational educational leadership and management theory and provides operational recommendations for school leaders and policymakers to sustainably enhance teacher effectiveness and institutional quality.